A Poetics of Simpson Pass: Natural History and Place-Making in Rocky Mountains Park - Krotz, Sarah Wylie (Studies in Canadian Literature / Études en littérature canadienne, 2014)
This essay examines A Sprig of Mountain Heather, an early pamphlet designed by J.B. Harkin and Mabel Williams to promote Canada’s dominion parks. Familiar in some historical circles but less so in literary ones, the pamphlet provides a fascinating glimpse into the colonial practice of natural history and its role in shaping European relationships to wild spaces such as Simpson Pass, on the border of Rocky Mountains (now Banff) Park. Containing both an actual specimen – a pressed flower from an alpine meadow on the pass – and “a story of the heather” that connects it to Scottish lore and culture, A Sprig of Mountain Heather demonstrates how natural history made it possible for European settlers to imbue even a remote and alien space with the homely resonance of place – a key attribute of the national parks’ colonial and curatorial relationship to wilderness. Read in the light of a wider history of botanical inventory and description both in the mountain parks and elsewhere in Canada, A Sprig of Mountain Heather exemplifies the potency of the natural object as a locus of memory that could at once transport and transplant emigrants, allowing them to establish a deeper connection to lands that were remote both geographically and culturally.